Struktura kapitałowa a rentowność kapitałów własnych zakładów ubezpieczeń na życie - Borda, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Among many different decisions taken in the financial management process of a life insurance company the significant role play decisions concerning the capital structure. The specific approach to a life insurance company's capital structure results from the technical reserves (especially life insurance reserves), which are devoted to cover present and future liabilities concerning the insurance contracts. In the paper the influence of the capital structure on financial security ad profitability of life insurance companies is considered. Moreover, the results of empirical research concerning the relation between capital structure, measured by technical reserves in proportion to equity, and return on equity in the case of life insurance companies operating in the Polish market are presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 34-41